Detection of novel potential regulators of stem cell differentiation and Cardiogenesis through Combined Genome-Wide profiling of Protein-Coding transcripts and microRNAs - Machado, Rui (2021)
In vitro differentiation of embryonic stem cells (ESCs) provides a convenient basis for the study of microRNA-based gene regulation that is relevant for early cardiogenic processes. However, to which degree insights gained from in vitro differentiation models can be readily transferred to the in vivo system remains unclear. In this study, we profiled simultaneous genome-wide measurements of mRNAs and microRNAs (miRNAs) of differentiating murine ESCs (mESCs) and integrated putative miRNA-gene interactions to assess miRNA-driven gene regulation. To identify interactions conserved between in vivo and in vitro, we combined our analysis with a recent transcriptomic study of early murine heart development in vivo. We detected over 200 putative miRNA–mRNA interactions with conserved expression patterns that were indicative of gene regulation across the in vitro and in vivo studies. A substantial proportion of candidate interactions have been already linked to cardiogenesis, supporting the validity of our approach. Notably, we also detected miRNAs with expression patterns that closely resembled those of key developmental transcription factors. The approach taken in this study enabled the identification of miRNA interactions in in vitro models with potential relevance for early cardiogenic development. Such comparative approaches will be important for the faithful application of stem cells in cardiovascular research.